Pain management with epidural catheter and epidural analgesia after spinal dorsal instrumentation of lumbar spine. Issue 7 (17th February 2023) - Hamed, Motaz; Asoglu, Harun; Lampmann, Tim; Winkelmann, Lena Marie; Salemdawod, Abdallah; Müller, Martin; Vatter, Hartmut; Banat, Mohammed; Eichhorn, Lars
Abstract : Spinal dorsal instrumentation (SDI) is an established treatment for degenerative spinal diseases. Adequate and immediate postoperative pain control is important for patient recovery and may be compromised by uncertainty about its efficacy and concern about early postoperative surgical complications or adverse events. The aim of the current study was to compare the use of epidural analgesia (EA) with systemic analgesia (SA) as regards pain reduction and early postoperative complications after SDI. Pain management with epidural or systemic analgesia in patients undergoing SDI by posterior approach between January 2019 and July 2020 was evaluated by clinical functional testing, measuring total opioid amounts used, and evaluating numerical rating scale values 24 and 96 hours postoperatively. The following were also monitored: demographic data, number of affected segments, length of hospital stay, inflammatory markers (leukocytes and serum C-reactive protein), early postoperative surgical complication rates, and adverse events. In total 79 patients were included (33 in the EA and 46 in the SA group). The SA group had significantly lower numerical rating scale values at days 1 to 4 after surgery ( P ≤ .001) and lower cumulative opioid use than the EA group ( P < .001). We found no difference in infection parameters, length of hospital stay or surgery-related complication rates. Our data demonstrate that epidural anesthesia was inferior to an opioid-based SA regime in reducing postoperative pain in patients undergoing spinal surgery. There is no benefit to the use of epidural catheters.